Immunosuppressive Isopimarane Diterpenes From Cultures of the Endophytic Fungus Ilyonectria robusta - Ke Ye; Xiao Lv; Xian Zhang; Pan-Pan Wei; Zheng-Hui Li; Hong-Lian Ai; Da-Ke Zhao; Ji-Kai Liu (Frontiers Media S.A., 2022)
Five new isopimarane diterpenes, robustaditerpene A-E (1-5), which include 19-nor-isopimarane skeleton and isopimarane skeleton, were isolated from the liquid fermentation of the endophytic fungus Ilyonectria robusta collected from Bletilla striata. The structure elucidation and relative configuration assignments of all compounds were accomplished by interpretation of NMR and HRESIMS spectrometric analyses and 13C NMR calculation. And the absolute configuration of 1-5 were identified by single-crystal X-ray diffraction and ECD calculation. Compound 3 inhibited lipopolysaccharide-induced B lymphocytes cell proliferation with an IC50 value at 17.42 ± 1.57 μM while compound 5 inhibited concanavalin A-induced T lymphocytes cell proliferation with an IC50 value at 75.22 ± 6.10 μM. These data suggested that compounds 3 and 5 may possess potential immunosuppressive prospect.